Infant feeding knowledge among women living with HIV and their interaction with healthcare providers in a high-income setting: a longitudinal mixed methods study - Ellen Moseholm; Inka Aho; Åsa Mellgren; Isik S Johansen; Terese L Katzenstein; Gitte Pedersen; Merete Storgaard; Nina Weis (BMC, 2024)
Abstract Background Recent changes in the infant feeding guidelines for women living with HIV from high-income countries recommend a more supportive approach focusing on shared decision-making. Limited information is available on the infant feeding knowledge of women living with HIV and how healthcare providers engage with them in this context. This multicenter, longitudinal, mixed methods study aims to get a comprehensive and nuanced understanding of infant feeding knowledge among women living with HIV of Nordic and non-Nordic origin living in Nordic countries, and their interaction with healthcare providers regarding infant feeding planning. Methods Pregnant women living with HIV in Denmark, Finland, and Sweden were recruited in 2019-2020. The Positive Attitudes Concerning Infant Feeding (PACIFY) questionnaire was completed in the 3rd trimester (T1), three (T2), and six (T3) months postpartum. Women who completed the quantitative survey were also invited to participate in qualitative semi-structured interviews at T1 and T3. Results from the survey and interviews were brought together through merging to assess for concordance, complementarity, expansion, or discordance between the datasets and to draw meta-inferences. Results In total, 44 women living with HIV completed the survey, of whom 31 also participated in the interviews. The merged analyses identified two overarching domains: Knowledge about breastfeeding in the U = U era and Communications with healthcare providers. The women expressed confusion about breastfeeding in the context of undetectable equals untransmittable (U = U). Women of Nordic origin were more unsure about whether breastfeeding was possible in the context of U = U than women of non-Nordic origin. Increased postpartum monitoring with monthly testing of the mother was not seen as a barrier to breastfeeding, but concerns were found regarding infant testing and infant ART exposure. Infant feeding discussions with healthcare providers were welcome but could also question whether breastfeeding was feasible, and many participants highlighted a need for more information. Conclusions Healthcare providers caring for women living with HIV must have up-to-date knowledge of HIV transmission risks during breastfeeding and engage in shared decision-making to optimally support infant feeding choices.